A House for the Catechumens: Public Conversions and Scandals in the Rise of the Jesuits - Kalak, Matteo Al (The catholic historical review, 2025)
This article will explore the origins of the House of Catechumens in Rome. After outlining the role played by Ignatius of Loyola, it will illustrate the political connections that enabled the Jesuits to activate a successful conversionist policy. The events related to the founding of the House, the changes to its governing statutes shortly after its establishment in 1543, and the period of coexistence with the Jesuit headquarters, which continued to host converts for several years, will then be reconstructed. Thanks to new documents, this article will finally shed light on the ambiguous figure of Don Giovanni da Torano, the first rector of the House of Catechumens.